The road to Woodstock - Lang, Michael (Ecco, 2009)
On the ground with the talent, the townspeople, and his handpicked crew, Woodstock organizer Lang had a unique and panoramic perspective of the festival which became legendary. Enhanced by interviews with others who were central to the making of the festival, this book tells the story from inspiration to celebration, capturing all the magic, mayhem, and mud in between.--From publisher description